Analysis of the Role of Manufacturing Industry in the Input-Output Economy - Simon; Patta Tope; Eddy Taqwa; Moh. Ichwan Tandju; Syamsuddin HM (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the structure of the manufacturing industry in Central Sulawesi, emphasizing intersectoral linkages and their contributions to output and gross value added. Using a quantitative approach based on input and output matrices, the study identifies strategic subsectors capable of generating high multiplier effects on the regional economy. The results indicate a shift in subsector dominance from agriculture and wood-based sectors to natural resource-based industries, particularly base metals and energy processing. This shift is accompanied by weakening forward linkages and increasing dependence on upstream sectors, indicating early signs of deindustrialization and limited manufacturing contribution to strengthening the domestic supply chain. The findings also indicate that only a few subsectors are capable of playing dual roles as users and providers of inputs between industries, narrowing the basis for structural transformation. The implication of this condition is the need for an industrial development strategy that encourages sector diversification, strengthens downstream processing, and improves connectivity between key subsectors. This study provides recommendations for policymakers to direct industrial development toward a more sustainable, inclusive, and long-term orientation, in order to encourage equitable and resilient regional economic growth amidst global dynamics.